Characterization of banana bunchy top virus on Sumatra (Indonesia) wild banana - Ruth Feti Rahayuniati; Sedyo Hartono; Susamto Somowiyarjo; Siti Subandiyah; JOHN E. THOMAS (Society for Indonesian Biodiversity, 2021)
Abstract. Rahayuniati RF, Hartono S, Somowiyarjo S, Subandiyah S, Thomas JE. 2021. Characterization of banana bunchy top virus on Sumatra (Indonesia) wild banana. Biodiversitas 22: 1243-1249. Banana bunchy top virus (BBTV) has been a major constrain on banana production worldwide. This virus infection is mostly found in banana cultivation.  The study aimed to characterize the BBTV on Sumatra wild bananas. The survey to collect seeds and typical symptomatic samples had been done in 2017 and 2019 in West Sumatra, South Sumatra, and Bengkulu. The transmission test of the virus was conducted by using the viruliferous vector on four wild banana species, while the identity of BBTV confirmed by nucleotide sequences analysis using primer pairs of DNA R and DNA S. Musa acuminata subsp. sumatrana (AA) have been found naturally infected by BBTV. The transmission confirmed on M. acuminata subsp. longipetiolata, M. acuminata subsp. malacensis, M. acuminata subsp. halabanensis and Musa sp. with typical bunchy top symptoms. The incidence on test plants were 40%, 80% 20%, 20% and 20%, respectively. The virus infection on Sumatra wild bananas prolonged the incubation periods in comparison to cv Mas. BBTV of M. acuminata subsp. sumatrana is similar to the BBTV MK940788 and MN073184 from Sumatra. This is the first report of BBTV on Sumatra wild banana. The result can be used as a reference to study the resistance of the banana against BBTV.